The Nexus Between Good/Bad Governance and Citizens’ Participation in Nigeria’s Electoral Process - Kelechi Johnmary Ani (E-Journal of Humanities, Arts and Social Sciences)
The place of the state in deciding the lives of the citizenry cannot be negotiated. This is because the first responsibility of the state is to protect the lives and properties of the citizenry. Ironically, the ability of the state to protect the lives and property of its citizenry would be measured on the level of governance impartation. When governance is good, the people will enjoy good life and smile but when the governance is poor, the masses will suffer. This study focuses on an assessment of the place of good/ bad governance in determining the nature of the electoral process in Nigeria. The study adopted a qualitative approach and used secondary data from other literature sources. The findings revealed that Nigeria is overtaken by bad governance and that has given fillip to electoral malpractice at all levels of the country’s election process. The study further revealed that the implication of the nexus between bad governance and electoral malpractice in the country include increased mortality rate, poverty and all manners of nepotism. The study concluded that bad governance in Nigeria has undermined the citizen’s participation in the electoral process. It recommends strategic steps like decentralization of the Nigerian state as well as digital elections and digital transmission of electoral results as the paths towards Nigerian national transformations. The study contributes to the wider body of literature in the area of politics, governance and policy analysis.